In vitro, in vivo, and in silico approaches for evaluating the preclinical DMPK profiles of ammoxetine, a novel chiral serotonin and norepinephrine reuptake inhibitor - Zhu, Xiuqing; Li, Yuexin; Luo, Huan; Zhang, Yunxia; Zhang, Zhenqing; Li, Jinglai (Frontiers in Pharmacology, 2024)
Background and Aim: Ammoxetine, a novel chiral serotonin and norepinephrine reuptake inhibitor, holds promise for major depressive disorder treatment. This study aimed to thoroughly investigate its preclinical drug metabolism and pharmacokinetics (DMPK) profiles.The preclinical DMPK profiles of ammoxetine were examined through in vitro, in vivo, and in silico methods.Results: Assessment of blood-brain barrier penetration via MDCK-MDR1 cells revealed strong brain permeation by ammoxetine, despite being a probable P-glycoprotein (P-gp) substrate.Molecular docking indicated a robust binding interaction between ammoxetine and P-gp.Ammoxetine was well absorbed orally, with Tmax ranging from 0.75-3.83 hours in rats and 0.75-1.40Preclinical DMPK profiles of ammoxetine hours in beagle dogs. At a 2 mg/kg dose in beagle dogs, ammoxetine exhibited an absolute bioavailability of approximately 42%. Plasma protein binding rates were around 50-60% in beagle dogs, rats, and humans, suggesting moderate binding. Tissue distribution studies displayed rapid and extensive ammoxetine spread in major rat tissues post-gavage, with notable brain exposure and no tissue accumulation. Cumulative excretion rates in rats' urine, feces, and bile accounted for only 1.11% of the total administered drug, indicating extensive transformation into metabolites. Chiral inversion of ammoxetine was absent in vivo. Metabolic stability varied across species using liver microsomes, but beagle dogs showed clearance rates more akin to humans. Metabolic pathways unveiled two key metabolites, M1 and M2. M1, likely generated through methylenedioxyphenyl ring oxidation, involves CYP2C19 and CYP3A4, crucial human cytochrome P450 (CYP) enzymes for liver metabolism, while M2 is M1's glucuronide conjugate. Ammoxetine may exhibit saturation elimination trends with increasing doses in rats and beagle dogs. A high-throughput assay using the cocktail-substrate method indicated weak CYP inhibition by ammoxetine on CYP2D6 and CYP1A2, with minimal effects on other CYP enzymes, suggesting a low likelihood of CYP inhibition-related drug-drug interactions.This study presents encouraging DMPK profiles of ammoxetine, backing its potential as a candidate compound for future clinical assessments.